Comparative study on specific H9N2 antibodies in broiler: Aida Bara Allawe and amen Ahmed Sabaar - Allawe, Aida Bara (The Iraqi Journal of Veterinary Medicine, 2009)
This study was concerned with conduction of experiment for this reason three groups of broiler chickswere used.First group (which is consisted of 15 chicks) was infected experimentally with H9N2(AMR.ANT/IRAQ/2005) (108.6 ELD50/0.1ml) at age (8) day. Second group (which is consisted of 15chicks) was infected experimentally with H9N2 (AMR.ANT/IRAQ/2005) (108.6 ELD50/0.1ml) at age(24) day. . The third group (which was consisted of 10 chicks) was considered as a control groupwithout infection. Immune response in all chicks groups was estimated at age (24, 44) days dependingon ELISA test.